A Ladder Architecture for Power Improvement and Multi-Peaks Elimination in PV Arrays during Non-Uniform Irradiance Scenarios - Satpathy P.R.; Babu Thanikanti S.; Krishna Madeti S.R.; Sharma R.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2024)
Solar Photovoltaic (PV) arrays are vulnerable to non-uniform irradiances that diminish their power generation and introduce complexities by creating multiple peaks in the power-voltage curves, ultimately leading to reduction in overall performance. Various mitigation techniques are proposed in the literature but, each exhibits limitations of cost, complexity, and application. Hence, to deal with such problems, in this paper, a ladder architecture for PV arrays is proposed to improve the power generation capability during non-uniform irradiance scenarios by using the charge redistribution approach. Also, the proposed ladder approach ensures the PV array to operates with convex characteristics and eliminates multiple peaks from the power curves. The proposed architecture is modeled and validated in the MATLAB/Simulink platform using a 9x3 array with system size of 8.8kW. The performance comparison under four partial shading cases is carried out with the conventional configurations using various comparison parameters. From the conducted analysis, the approach is found to significantly improve the array power generation and generate convex curves with higher than 99% conversion efficiency. 2023 IEEE.